Barrier Factors In Maintaining Breastmilk Volume - Imelda Iskandar1, Suryani As’ad2, Nasrudin Andi Mappaware3, EmaAlasiry4, AzniahSyam5, Suradi Efendi6 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: Breast milk (ASI) is a nutrient that is produced from cellular secretion and transportationactivities in the breast organs. The development cycle of the organ of ASI secretion begins to form fromthe neonate, puberty to pregnancy 1. Until now, several assumptions that state that the production ofbreastfeeding of a nursing mother are influenced by various external and internal factors. External factorsinvolve the environment, sociodemography, and even sociocultural2.Method: The volume of milk assessed on days 7th, 8th, 9th, postpartum. Milk volume measured throughpumping using a Medela Swing Double Pump electric breast pump for 15 minutes, the weighted milk isthen returned for drinking to the baby using new media (spoon or cup feeding). Sociodemographic variables,obstetric history, and lactation history were measured using an observation form, postpartum is then groupedinto two groups; breastfeeding mothers with optimal and sub-optimal milk production. The relationshipbetween variables was tested by the chi-square test and logistic regression test.Results: Occupational variables (p <0.049; OR = 2.61), initiation of early breastfeeding (p <0.022; OR =2.73), frequency of breastfeeding (p <0.003; OR = 4.62), duration of breastfeeding (p <0.018; OR = 2.76)demonstrates relationship with milk volume.Conclusion: This research succeeded in proving several external factors such frequent and timing thatsupported the mechanical mechanism of breast milk production.